Asian Political Cartoons - Lent, John A. (Book collections on Project MUSE., 2023)
"In Asian Political Cartoons, scholar John A. Lent explores the history and contemporary status of political cartooning in Asia, including East Asia (China, Hong Kong, Japan, North and South Korea, Mongolia, and Taiwan), Southeast Asia (Brunei, Cambodia, Indonesia, Malaysia, Myanmar, Philippines, Singapore, Thailand, and Vietnam), and South Asia (Bangladesh, India, Iran, Nepal, Pakistan, and Sri Lanka). Incorporating hundreds of interviews, as well as textual analysis of cartoons; observation of workplaces, companies, and cartoonists at work; and historical research, Lent offers not only the first such survey in English, but the most complete and detailed in any language. Richly illustrated, this volume brings much-needed attention to the political cartoons of a region that has accelerated faster and more expansively economically, culturally, and in other ways than perhaps any other part of the world. Emphasizing the "freedom to cartoon," the author examines political cartoons that attempt to expose, bring attention to, blame or condemn, satirically mock, and caricaturize problems and their perpetrators. Lent presents readers a pioneering survey of such political cartooning in twenty-two countries and territories, studying aspects of professionalism, cartoonists' work environments, philosophies and influences, the state of newspaper and magazine industries, the state's roles in political cartooning, modern technology, and other issues facing political cartoonists. Asian Political Cartoons encompasses topics such as political and social satire in Asia during ancient times, humor/cartoon magazines established by Western colonists, and propaganda cartoons employed in independence campaigns. The volume also explores stumbling blocks contemporary cartoonists must hurdle, including new or beefed-up restrictions and regulations, a dwindling number of publishing venues, protected vested interests of conglomerate-owned media, and political correctness gone awry. In these pages, cartoonists recount intriguing ways they cope with restrictions-through layered hidden messages, by using other platforms, and finding unique means to use cartooning to make a living"--